2012
DOI: 10.5505/tjtes.2012.67044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epidural anesthesia on anastomotic leakage in colonic surgery: experimental study

Abstract: AMAÇBir hayvan modelinde, sürekli epidural anestezi ile kolon anastomozunun gücü arasındaki ilişki araştırıldı. GEREÇ VE YÖNTEMBeyaz erkek 14 adet Yeni Zelanda tavşanı çalışmaya alındı ve randomize iki grup oluşturuldu. Grup 1'de (n=7) epiduralden sürekli olarak %0,9'luk NaCl infüzyonu (0,4 mlkg -1 bolus ve 0,2 mlkg -1 sa -1 infüzyon) ve Grup 2'de (n=7) epiduralden sürekli olarak %1'lik lidokain infüzyonu (0,4 mlkg -1 bolus ve 0.2 ml kg -1 sa -1 infuzyon) uygulandı. İnfüz-yonlara, operasyonların başında başlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The relationship between any potential reduction in anastomotic perfusion and anastomotic leakage remains unproven. In a study of 14 rabbits allocated to epidural or control, epidural analgesia for 6 h after surgery produced significantly higher anastomotic bursting pressures on day four2. This study, although small, suggested a protective effect of epidurals against anastomotic leakage.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The relationship between any potential reduction in anastomotic perfusion and anastomotic leakage remains unproven. In a study of 14 rabbits allocated to epidural or control, epidural analgesia for 6 h after surgery produced significantly higher anastomotic bursting pressures on day four2. This study, although small, suggested a protective effect of epidurals against anastomotic leakage.…”
Section: Discussionmentioning
confidence: 69%
“…This, it has been suggested, might affect anastomotic perfusion, although any effects on subsequent anastomotic leakage remain unproven1. Indeed, one animal study demonstrated an increase in anastomotic bursting pressures with epidural analgesia2.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the epidural and spinal administration of bupivacaine have shown no significant effect on ABP. [ 22 , 23 ] In an experimental study by Adanır et al,[ 24 ] despite no significant change in hydroxyproline levels with epidural lidocaine, increased ABP and durability of colon anastomosis were reported. Similarly, in the experimental study by Camargo et al,[ 4 ] peritoneal application of bupivacaine showed a non-significant decrease in Total Energy Rupture test levels in the absence of peritonitis.…”
Section: Discussionmentioning
confidence: 99%